In Memoriam: Deon Visser 1953-2016 - van der Waag, Ian (Scientia Militaria - South African Journal of Military Studies, 2016)
We learned with great sadness that Lieutenant Colonel Deon Visser, who joined the Military Academy community in 1986, passed away on 23 May 2016. Deon was a close colleague, a kind and loyal friend, a respected military officer, and an esteemed military historian. He was these things to all who knew him.